El fervor democrático quiteño: ¿un mito, un sueño o algo sustancial? - Bustamante, Teodoro (2005)
This paper suggests that the discourse about the April revolt in Ecuador is a mechanism to reintroduce those events in a mythic, dichotomist comprehension of Ecuadorian political reality. In this proccess, the disruptive content of the revolt, the affirmation of democracy in a society that denies it, is diluted.